Integrasi Kearifan Lokal Bali dalam Buku Ajar Sekolah Dasar - I Made Sudiana; I Gede Sudirgayasa (Pusat Kajian Bali Universitas Udayana, 2015)
AbstractIntegration of Balinese local wisdom required to maintainthe noble values of Balinese culture through early education.One of them is to do a primary school textbook developmentthat is integrated with the Balinese local wisdom as analternative. Therefore, this study was conducted to examinea wide range of Balinese local wisdom with regard toprimary school education. This is a development research.Initial data collection is done with the study of documents,interviews, and questionnaires. The elementary school isused as a source document and the respondent amountedto six elementary schools representing urban, suburban,and rural. Based on the preliminary data analysis, prepareda textbook draft. Assessment is done with a texbook draftfeasibility assessment instruments adopted from the bookassessment instruments by National Education StandardsAgency. Analysis of results of the assessment carried outby qualitative descriptive with the help of Microsoft OfficeExcel 2007. Based on the results of research and discussion,it can be concluded, that there are a lot of Balinese localwisdom with values that can be integrated in primary schooleducation. The results also show that the integrated Balineselocal wisdom textbook draft classified as good and feasibleto implement.